(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Marking the 10th anniversary of Kyrgyzstan’s membership in the Eurasian Economic Union (EAEU), this article assesses the country’s transport integration within the bloc. It evaluates the EAEU’s transport policy outcomes for Kyrgyzstan as a landlocked nation and proposes measures to enhance future cooperation.